Secular trends in innovation and technological change - Rainer Frietsch; Torben Schubert; Peter Neuhäusler (Expertenkommission Forschung und Innovation (EFI), 2017)
This paper deals with the question of changing relations between business R&D (BERD), patents and output measures like value added and productivity (macro level) as well as EBIT and market capitalization (micro level) to analyze long-term/secular effects of technological change at different levels. The results of the panel data reveal an increase of the patent numbers resulting from R&D expenditures. However, we also find a difference in the elasticities of BERD and patents between patent-intensive and non-patent-intensive sectors. In addition, the association between patents and labor productivity falls when all sectors are taken into account, implying decreasing contributions of technological progress to the productivity. Yet, the drivers are non-patent-intensive sectors, as we observe an increasing association of patents and labor productivity for patent-intensive sectors. The results of the enterprise panel data reveal similar results. The correlations between R&D and patents increased over the last 20 years, although it seems there is a concentration of R&D and patenting activities to a smaller amount of firms, which can partially be explained by the fact that research and development that is necessary for a single patent has become more and more expensive in the past years.
Keywords: 330